The theory of thermodynamic and magnetic properties of multi-band superconductors - Palistrant, M.E. (Condensed Matter Physics, 2009)
The main stages of development of the theory of superconducting systems with overlapping energy bands are
formulated. The main references of the classical papers of the authors of this theory (Prof. V.A.Moskalenko and
his co-workers) are listed.The list also includes papers related to high-temperature superconductivity. Some
peculiarities of the two-band model, which give qualitatively new results in comparison with the usual oneband
model, are described.The application of the two-band model for the description of the thermodynamical
and magnetical properties of the compound MgB₂ is also discussed. Формулюються основнi стани розвитку теорiї надпровiдних систем iз енергетичними зонами, що перекриваються. Приводяться основнi поклики на класичнi роботи авторiв цiєї теорiї (проф. В.А. Москаленко та його спiвробiтники) доповнений iншими роботами з високотемпературної надпровiдностi. Описано певнi особливостi двозонної моделi, що приводять до цiлком нових результатiв у порiвняннi з однозонною моделлю. Обговорюються можливостi використання двозонної моделi до опису термодинамiчних i магнiтних властивостей сполуки MgB₂.